2018
DOI: 10.1007/s00464-018-6055-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel technique to manage gastrointestinal leaks with endoluminal negative pressure: a single institution experience

Abstract: Our experience demonstrates that EVAC therapy is feasible and effective for the management of gastrointestinal perforations/leaks throughout the GI tract and can be considered as a safe alternative to surgical intervention in select cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Nineteen series were finally selected for the present analysis. Overall, the quality of the included studies is low – eight retrospective series , six prospective , the design was not reported in four , and there was one case report . Two of them were small comparative series , and three were multicentre studies .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nineteen series were finally selected for the present analysis. Overall, the quality of the included studies is low – eight retrospective series , six prospective , the design was not reported in four , and there was one case report . Two of them were small comparative series , and three were multicentre studies .…”
Section: Resultsmentioning
confidence: 97%
“…A total of 114 publications were found. Thirty of them, published between 2006 and 2018, were considered relevant . Four were excluded because they reported overlapping cases and only the most recent series were included .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, reports of endoluminal negative pressure treatment have frequently used. It is the method that can treat the AL with minimal invasion by using sponge trans-anal in abscess and apply continuous negative pres-sure to close the abscess cavity [4][5][6][7][8] . However, according to a review by G.I.Popivanov et al, there were 84.5% patients who needed to create stoma, and 72.6% patients underwent stoma closure.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several retrospective studies on ENPT have reported on more than 300 patients with esophageal defects of varying etiology [718, 2023, 25]. Healing rates range from 60 to 100% (Table 1).…”
Section: Enpt In the Esophagusmentioning
confidence: 99%